Pengembangan Sistem Informasi Laporan Produksi Berbasis Web Menggunakan Metode Rapid Application Development (RAD) Pada PT. Nichias Metalwork Indonesia - Zaenur Rozikin; Edi Hotman Sijabat (DPPM Universitas Pelita Bangsa, 2024)
In general, production management consists of several functions in which management experts give their respective opinions. From the problems that exist in PT. Nichias Metalwork Indonesia in production, the process of inputting production report data still uses sheets of paper which are done manually and then collected at the supervisor's desk, and hinders the process of inputting data by the admin, because the admin has to take the report sheets that are on the supervisor's desk. The method used in this study is the Rapid Application Development (RAD) method. The Rapid Application Development method is a software development method that emphasizes development in a short time and uses iterative (repetitive) methods where the working model is constructed at the early stages of development to determine user requirements. In making the production report system the author uses the PHP Programming Language and MySQL database. The purpose of this study is to design and build a production reporting information system to make it easier to check and input goods to minimize the difference in production inventory and speed up the process of inputting and reporting production at PT. Nichias Metalwork Indonesia